Improvement of Train Traffic Control Technology Based on Abstract Modelling of Operational Processes - Lavrukhin, O. V.; Myronets, S. R; Bohomolov, V. A. (Science and Transport Progress, 2022)
Purpose. The main goal of the work is to improve the process of controlling transport units (trains) on the basis of abstract modelling of operational processes, which will allow the operational dispatching apparatus to respond in a timely manner to constantly changing train conditions. Methodology. In order to ensure the rhythmic and uniform movement of trains of all categories along railway lines, train dispatchers, based on their experience, together with locomotive dispatchers and train locomotive drivers, constantly monitor the operational train condition and develop a strategy for the movement of trains along railway sections. This approach is quite energy-consuming in terms of human resources due to excessive nervous tension. As a result of this shortcoming and mistakes made, there are unproductive downtime at railway stations and, in some cases, a significant reduction in sectional speed, which in turn directly affects the industry's profitability and the quality of passenger service, including high-speed traffic. The basis for making management decisions on operational train conditions is automated systems and personal experience of professionals. In this regard, it is advisable to form a model that will reproduce the optimal train operation plan by predicting the main indicators. Findings. In the course of the scientific and applied research, the predictor of collision of trains of different categories with station and inter-train intervals was determined, which can later become the basis of a powerful module of the operational decision support system. Originality. The paper proposes an approach to improving the process of managing transport units based on abstract modelling of operational processes, which, unlike existing approaches, allows the implementation of a high-speed intelligent decision support system for railway dispatching with the possibility of self-adaptation. Practical value. The implementation of the proposed approach in the form of an automated software system will further increase the profitability of the railway industry in the freight and passenger traffic sector.